United Republic of Tanzania : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2006)
This paper examines the United Republic of Tanzania's Fifth Review Under the Poverty Reduction and Growth Facility. Economic growth, inflation, and the external position have been evolving in a manner broadly consistent with program assumptions. For the medium term, challenges center on mobilization and efficient use of public resources, managing liquidity pressures from high aid inflows, and facilitation of private sector-led growth, while maintaining a sound macroeconomic framework. The government is actively considering measures to address the crisis situation in the energy sector.